Evaluation of the in vitro antibacterial activity of the extracts of Caesalpinia spinosa “tara” and Eucalyptus sp. "eucalyptus" - Liu B., Humberto (2022)
The antibacterian activity of extract of Caesalpinia spinosa and Eucalyptus sp. "eucalipto" was valued using bacterials capes gram positives (Staphylococcus aureus and Bacyllus subtilis) and gram negatives (Escherichia coli, Klebsiella sp, Shigella flexneri).For the investigation was used as extraction solvent a mixture of aIcohol-acetona (1:1), the biological activity of the obtained extracts was valued using the disc diffusion technique.The fruit peel of Caesalpinia spinosa and the leaves of Eucalyptus sp show a selective activity over the valued grampositives bacteriums.